Anisotropic phonon dispersion and optoelectronic properties of few-layer HfS2. Issue 7 (2nd February 2023) - Muhammad, Zahir; Wali, Faiz; Hussain, Ghulam; Islam, Rajibul; Ullah, Sami; Wu, Peng; Khan, Firoz; Autieri, Carmine; Zhang, Yue; Alshahrani, Thamraa; Zhao, Weisheng
Abstract : Few layer HfS2 flakes are studied by temperature, excitation and polarization-dependent Raman spectroscopy. In contrast, the fabricated device shows considerable photodetection properties under light laser power illumination. Abstract : The phonon dispersion of mechanically exfoliated two-dimensional (2D) HfS2 is investigated through angle-resolved Raman spectroscopy and supported by first principles density functional theory (DFT) calculations. The Raman spectra show four active modes with two optical modes related to the in-plane motion of hafnium (Hf) and sulfur (S) and the surface translation of S or due to surface phonons. The vibrational frequencies are redshifted, and their intensity decreases from bulk to monolayer due to van der Waals interaction and interlayer forces and resonance effects, respectively. At the same time, the phonon modes are softened at varying temperatures, which can be attributed to anharmonic phonon–phonon interaction and the contribution of thermal expansion. In contrast, the estimated enhanced surface temperature can't damage the lattice structure at high laser heating. At various detection angles, different intensities of the phonon modes determine the crystallographic orientation and the anisotropic behaviour of 2D HfS2 . Moreover, the fabricated electrical device on few-layer HfS2 shows interesting electrical and photodetection properties. The ON–OFF ratio increased from ∼0.8 × 10 4 to ∼8 × 10 4 ; mobility increased from 24.8 cm 2 V −1 s −1 to 211 cm 2 V −1 s −1, and photocurrent increased five times via changing from dark to 532 nm of incident light. The photoresponse time of the device is further enhanced by laser light illumination. These results provide a detailed perspective of 2D HfS2, which implies better phonon propagation for thermoelectric, 2D material-based phototransistors for electronic and optoelectronic applications.